Rekomendasi Pemberian Kredit Pemilikan Rumah Menggunakan Kombinasi Metode VIKOR dan Pembobotan Entropy - Irmansyah Lubis, Ahmadi; Siregar, Rosma (Journal of Computer System and Informatics (JoSYC), 2024)
Home Ownership Credit (KPR) is the process of buying a house by way of credit or installments for a certain period of time and a determined interest rate. Problems that often arise in the process of granting mortgages are when providing an analysis of recommendations for the suitability of a house, such as credit analysis errors which often result in bad credit payments and disrupt the fund circulation system between credit payments and receivables. Billing. In addition, there is no filter in determining the eligibility of providing credit computerized, the system is equipped with a decision support system that can describe the supporting factors that are used as a calculation weight in making decisions on determining home ownership loans for those who deserve to receive them. To analyze the feasibility of providing home ownership loans, a decision support system is needed that can provide a good analysis to determine the creditworthiness of home ownership with the VIKOR method and the Entropy method. The Entropy method is applied to determine the weight of each criterion and the VIKOR method is used to rank alternatives. Based on the results of the study, the VIKOR method and the Entropy weighting method can provide recommendations for providing home ownership loans to eligible customers based on specified criteria. The ranking results were obtained by testing variations in the VIKOR index value with the best alternative result, namely A3 (3rd Alternative). And the Entropy method produces objective and proportional criteria weights and obtains valid criteria weights without having to give criteria weights manually or subjectively, so it is useful for determining the weight of criteria that need not be doubted about their validity.